Laborscapes and Archaeologies of Sustainability: Early Globalization and Commercial Farming in the San Pasquale Valley, Calabria, Italy from AD 1800–2018. (9th July 2019) - Chesson, Meredith; Ullah, Isaac; Ames, Nicholas; Benchekroun, Sarah; Forbes, Hamish; Garcia, Yesenia; Iiriti, Giovanni; Lazrus, Paula; Robb, John; Squillaci, Maria; Wolff, Nicholas
Abstract : Archaeological research on sustainability enjoys an increasingly high profile in the discipline, with scholars employing a range of methodological and theoretical platforms. We argue that the most successful forays of applied archaeological research into sustainability encompass three major realms: the social foundations and local histories of any human community, the economic resources and practices to support that community, and the environmental and geological couplings existing therein. This study explores dynamic relationships between these three spheres by discussing how nineteenth- and twentieth-century farmers, land managers, and landowners, along with their families, created and maintained a vibrant community, founded for the commercial production of bergamot, mulberries, olives, grapes, and a wide variety of fruits, nuts, vegetables, and cereal crops in the San Pasquale Valley (SPQV), Calabria, Italy. Our theoretical approach combines Lave and Wenger's (1991) community of practice approach with Scarborough's (2009) model of labor- and techno-tasking strategies to document laborscapes through time, using architectural documentation, oral histories, documentary evidence, oral histories, ethnographic interviews, and climate modeling. We demonstrate the interpretive power of incorporating cultural foundations into environmental and economic models to produce more comprehensive understandings of how people succeed and fail to sustain livelihoods and communities. We argue that rhythms and nuances of linkages between the SPQV environment, economy, and social worlds require a more flexible conceptualization of sustainability to encompass the variety of solutions developed by current SPQV community members to craft sustainable economic and social futures for themselves.